Competencies of Teachers' use of Technology in Learning and Teaching Processes - AKÜNER, MUSTAFA CANER (KAUNAS UNIV TECHNOLOGY, 2012)
This research has been done on how the teachers will use technology in teaching-learning processes. Teachers' use of educational technologies in teaching-learning processes has caused alteration in teaching qualification and teacher role. Technology has enabled students to learn in more different dimensions by removing time-place limitations in teaching and learning. Teachers have not only been the source of information as in traditional education methods, but also advisors, counselors and pathfinders who guide students to information and redirect them at reaching information. Using technology in education can be possible via its integration to teaching-learning processes, so teachers use technology in arranging teaching-learning processes. Utilized technology is selected harmoniously for education purposes and environments. Technology must be such as to supply teaching-learning process, not a basis model, and must be eligible to be integrated into teaching-learning processes.
Keywords: Education technology; teaching process; technology learning; teacher training; use of technology